Role of Patient’s Age and Comorbidities in Therapy of Chronic Lymphocytic Leukemia - VV Strugov; EA Stadnik; YuV Virts; TO Silina; AYu Zaritskii (Клиническая онкогематология)
Background & Aims. New schemes of the antitumor therapy of CLL resulted in improvement of survival of relatively young patients. However, the therapy outcomes of elderly patients are still unsatisfactory. Erroneous overestimation of expected toxicity of standard therapeutic regimens in some elderly patients may play a certain role, thus leading to prescription of less effective regimens. Therefore, the urgent problem is to find objective criteria for risk stratification in CLL. The aim of the study is to evaluate the prognostic significance of patient’s age and the CIRS-G index in elderly patients treated with fludarabine-containing regimens in first line treatment outside clinical trials.